EVALUATION OF THE PERFORMANCE OF BIOSPHERE COMPATIBLE CITY FUNCTIONS IN MODERN RESIDENTIAL AREAS - Bakaeva, Natalia Vladimirovna; Chernyaeva, Irina Viktorovna; Vorobyev, Sergey Alexsandrovich (Journal of Applied Engineering Science, 2017)
The article discusses the issues of city construction policy in the field of urban infrastructure planning, design and construction of modern residential areas from the perspective of city and settlement biosphere compatibility. The authors propose a technique for calculating generalized criteria for the biosphere compatibility of urban environment; give systematized constituents of city infrastructure when evaluating the performance of city functions in modern residential areas. The gradation of the levels of performance and availability coefficients is carried out. The developed technique is an integral part of the methodology for urban infrastructure development planning. Numerical performance of the biosphere compatible city functions is shown; its analysis is carried out based on the data of one of the new residential areas of a large Russian city. The authors come to the conclusion concerning the fundamental necessity of adopting a new innovation city planning policy.